A closed-loop recovery strategy of unsaturated polyester composite: Bridging heterogeneous catalyst and resin by noncovalent interactions. (10th November 2022) - Wang, Baolong; Shen, Yibo; Lu, Fei; Xu, Ningdi; Liu, Yingying; Li, Da; Li, Jun; Huang, Yudong; Hu, Zhen
Abstract: Heterogeneous catalysis has been shown to effectively degrade organic pollution. However, it is challenging to degrade the thermosetting unsaturated polyester resin (UPR) because the contact mode between heterogeneous catalyst and resin leads to an inefficient degradation. Meanwhile, the inevitable degradation products also cause the generation of waste chemicals. Herein, the efficient degradation and closed-loop recovery strategy of UPR composite were carried out by enhancing the contact areas through bridging heterogeneous catalyst and resin. Based on hydrolysis reaction, the controllable decomposition of crosslinking UPR was utilized to yield carboxyl-rich and hydroxy-rich copolymers, forming a porous structure. With the induction of tertiary butanol ( t BuOH), a heterogeneous bimetallic Co–Fe Prussian blue analogue catalyst was thus immobilized onto the hydrolyzed resin due to the hydrogen bonds and Van der Waals force, which confirmed by experiment and theoretical calculation. The catalyst subsequently activated H2 O2 to generate radicals that could effectively degrade resin by triggering strong chemical bond cleavage. It was optimized that more than 90% UPR was decomposed at 100 °C below. Notably, the remarkable nondestructive recovery process of woven carbon fiber (CF) from composite was well demonstrated. The recycled CF and its reinforced composite exhibited more than 90% strength retention to the virgins. Besides, the degradation products were employed into waterborne coating with superior properties. This work provides an efficient and feasible catalytic strategy for closed-loop recovery of UPR composite. Graphical abstract: Herein, an efficient catalytic degradation strategy which the heterogeneous PBA catalyst was immobilized onto the resin via noncovalent interactions was explored for closed-loop recovery of UPR composite. Image 1 Highlights: The PBA catalyst could be immobilized on the HUPR due to the noncovalent interactions. Radical was generated around the immobilized catalyst, increasing the weight loss of HUPR significantly. Thermosetting UPR could be degraded more than 90% under 100 °C, which was superior to other references. The CF cloth in UPR composites could be nondestructively recycled and reusable via this efficient degradation strategy.